2023
DOI: 10.1177/2632010x231184329
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Tumor Budding on Moroccan Gastric Cancer Patients

Souhaila El Yaagoubi,
Meryem Zaryouhi,
Soumaya Benmaamar
et al.

Abstract: Background: Tumor budding (TB) has been defined as an independent prognostic factor in many carcinomas like colon adenocarcinoma, but its prognostic impact on gastric cancer patients remains not well established. In the present study, we aimed to highlight the correlation of tumor budding with clinicopathological features and predict its survival outcomes in gastric cancer patients for the first time in the Moroccan population. Methods: This study was conducted on 83 patients who underwent surgery for gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In fact, although TNM classification remains the gold standard for prognostic stratification of colorectal cancer patients, heterogeneity in survival within the same stages required additional markers [23][24][25][26]. Several authors have found tumor budding to be independently associated with disease recurrence, cancer-related death and reduced overall survival (OS) [27][28][29][30][31][32][33][34][35]. In the setting of liver metastases, few data have been reported [36][37][38], and the main issue is that the only way to assess this pathological marker is in a surgical specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, although TNM classification remains the gold standard for prognostic stratification of colorectal cancer patients, heterogeneity in survival within the same stages required additional markers [23][24][25][26]. Several authors have found tumor budding to be independently associated with disease recurrence, cancer-related death and reduced overall survival (OS) [27][28][29][30][31][32][33][34][35]. In the setting of liver metastases, few data have been reported [36][37][38], and the main issue is that the only way to assess this pathological marker is in a surgical specimen.…”
Section: Discussionmentioning
confidence: 99%
“…However, strong correlations between the KRAS/BRAF mutational status and tumor budding have been reported [36]. So, patients with liver metastases with tumor budding and/or KRAS mutational status [39,40] respond poorly to anti-EGFR therapy [32]. In the context of personalized medicine, this is evident as the possibility to predict several prognostic markers allows us to identify the best treatment for a specific patient [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%